Rev Pungula Wellington Dingani – Leadership in the Corinthian Church in Phepheni, Eastern Cape, South Africa - Barnard, Marcel; Nell, Ian; Mbaya, Henry (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Local leadership is crucial in Africa. This article focuses on leadership in African Independent Churches, more specifically on the leader of a local congregation of the Corinthian Church, Rev Dingani in Phepheni, Eastern Cape. The article is composed of two parts. The first part is a portrait of Dingani, mainly from an emic (inside) point of view. After a biographical sketch, his ministry and liturgical leadership are outlined, followed by a portrait of Rev Dingani as a theologian. The second part, which mainly takes an etic (outside) stance, places this portrait in a wider context of leadership in African Independent Churches and sub-Saharan Africa as a whole. After indicating some general features of African leadership, the article focuses more specifically on two leadership styles: 1. The humane-oriented and charismatic/value-based style. 2. The participative and autonomous style. By distinguishing this emic and etic positions, we confront Western and African epistemologies, without reconciling them in advance.